Respiratory Syndrome Coronavirus Infections: Possible Mechanisms of Neurological Implications—A Systematic Review - de Assis, Gilmara Gomes; Murawska-Cialowicz, Eugenia; Cieszczyk, Pawel; Gasanov, Eugene V. (Frontiers in Neurology, 2020)
In the context of the worst Pandemic of the century – Covid-19 – emerged in China and reached the whole globe in last than 6 months, knowledge about virus behavior that could serve for prognostication is extremely required. Following the patterns of other Coronaviruses (CoVs), in particular of those infecting the respiratory tract, doctors have already reported neurological manifestations in Covid-19 patients that require attention to the neurovirulence of this SARS-CoV2. In order to collect all available information on the implications and mechanisms of infections by respiratory-virulent CoVs, a systematic review was designed following PRISMA protocol, regarding the PICO’s strategy: P – Healthy individuals, Patients, human-specific viruses susceptible animal models; I – Molecular, cell cultures, and comparative experimental studies; C – Healthy, disease and immunized conditions; O – respiratory-virulent CoV virulence and pathogenicity for the CNS. The search was conducted in PubMed databases from 30th March to 1st April 2020. Results indicate the involvement of CNS in infection by various CoVs. Infection begins in airway epithelia with subsequent alveolar involvement then virus spread to the CNS via neuronal contacts with the recruitment of the axonal transport. The neuronal infection and losses by regulated cell death are a main factors causing generalized encephalitis.